Implementation of wavelet codec by using Texas Instruments DSP TMS320C6701 EVM board - Abd Manap, Nurulfajar (IEEE, 2001)
This paper describes the implementation of the wavelet codec: (encoder and decoder) by using the Texas Instruments DSP (digital signal processor) TMS320C6701 on the EVM (evaluation module) board. The wavelet codec is used to compress and decompress gray scale images for real time data compression. The wavelet codec algorithm has been transferred into C and assembly code in the Code Composer Studio in order to program the 'C6xx DSP. The capability of the 'C6xx to change the code easily, correct or update applications, reduces the development time, cost and power consumption. With. the development tools provided for the 'C6xx DSP platform, it creates an easy-to-use environment that optimizes the devices' performance and minimizes technical barriers to software and hardware design